Cerebral cavernous malformation - Beržanskis, Mindaugas; Macytė, Dovilė; Šustickas, Gytis (Lietuvos chirurgija, 2017)
Cerebral cavernous malformations (CCM) are low-flow vascular lesions in eloquent locations. Their presentation is often marked with symptomatic hemorrhages. Annual brainstem CM rate of hemorrhage is from 2.3% to 4.1%. Surgery for deep-seated or brainstem lesions is less successful and is associated with an early morbidity rate of roughly 30–70% and a mortality rate of 2%. Signs and symptoms of CCM depends on localization in the brain. Approximately 80% of cases are supratentorial cavernomas. The most frequent injuring zones are frontal, temporal lobes and subcortical region. The most common symptoms are epilepsy and seizures. Also it can effect motor fibers which are situated in the cerebellum branch. Statistically approximately 40% all of CCM are asymptomatic and found accidentally when radiological investigations are taken. A preoperative MRI is essential for understanding the anatomy of the lesion and complete surgical resection of CCM is the only management strategy that can be fully curative. A non-radical resection of CCM is associated with high recurrence risk. From 12% to 17% patients may manifest a neurological deficits after surgery. Permanent neurological deficit rate is 2.6–8%. It consists of symptoms such as severe headache, mild speech dysfunction, ataxia, severe hemiparesis, sensorical dysfunction. MRI is the most sensitive and specific diagnostic test for cerebral cavernous malformations. CCMs can be very small and difficult to identify on routine brain MRI. Due to hemosiderin associated with these lesions, there is marked “blooming” view, resulting in much higher sensitivity for lesion detection.